Bandwidth enhancement of a microstrip-line-fed printed wide-slot antenna. - Jia-Yi Sze (IEEE Transactions on antennas and propagation)
Printed wide-slot antennas fed by a microstrip line with a fork-like tuning stub for bandwidth enhancement are proposed and experimentally investigated. Both the impedance and radiation characteristics of this antenna are studied. Experimental results indicate that a 1:1.5 VSWR bandwidth of 1 GHz is achieved at operating frequencies around 2 GHz, which is nearly ten times that of a conventional microstrip-line-fed printed wide-slot antenna. It also achieved a 2-dB gain bandwidth of at least 0.5 GHz